Sickness absenteeism of Primary Health Care professionals before and during the COVID-19 pandemic - Garbin, Artênio José Ísper [UNESP]; Nascimento, Carolina Carvalho Menez Pinto [UNESP]; Zacharias, Fabiana Costa Machado; Garbin, Cléa Adas Saliba [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP] (FapUNIFESP (SciELO), 2022)
OBJECTIVE: to identify the frequency of occurrence of sickness absenteeism, according to the profile of Primary Health Care (PHC) professionals, and verify if there was an impact of the pandemic on absence duration and reason. METHODS: a cross-sectional study, from January/2019 to December/2020, with PHC professionals from a municipality in northeastern São Paulo. Descriptive statistics were performed, with frequency calculation. RESULTS: of the 977 PHC professionals, 633 (64.79%) used a medical certificate to justify their absence from work in 2019, and 837 (85.67%) in 2020. The main reason for leave was diseases of the musculoskeletal system and connective tissue in the two years. The mean duration of leave was 7.33 days (SD=17.33) in 2019 and 9.88 days (SD=16.05) in 2020. Nursing assistants were the ones who took the most leave in both years. CONCLUSIONS: there was an impact of the pandemic on absence duration and reason.